1980
DOI: 10.1021/bi00545a016
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of 3-(3,4-dihydroxyphenyl)alanine decarboxylase by 2-(fluoromethyl)-3-(3,4-dihydroxyphenyl)alanine

Abstract: 2-(Fluoromethyl)-3-(3,4-dihydroxyphenyl)alanine [alpha-FM-Dopa (I)] causes rapid, time-dependent, stereospecific, and irreversible inhibition of hog kidney aromatic amino acid (Dopa) decarboxylase. The inactivation occurs with loss of both the carboxyl carbon and fluoride from I and results in the stoichimetric formation of a covalent enzyme-inhibitor adduct. The data are consistent with I being a suicide inactivator of the enzyme, and a plausible mechanism for the inactivation process is presented. The inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…TDC from certain plants has been shown to be strongly inhibited by a-fluoromethyl-3,4-dihydroxyphenylalanine (a suicide inactivator [12]) and by the phenylalanine analog AOPP (2). Eschscholtzia TDC was largely unaffected by preincubation with a-fluoromethyl(3,4-dihydroxyphenyl)-alanine and difluoromethyl-tyrosine (Table IV) but was inactivated by AOPP (Table IV; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TDC from certain plants has been shown to be strongly inhibited by a-fluoromethyl-3,4-dihydroxyphenylalanine (a suicide inactivator [12]) and by the phenylalanine analog AOPP (2). Eschscholtzia TDC was largely unaffected by preincubation with a-fluoromethyl(3,4-dihydroxyphenyl)-alanine and difluoromethyl-tyrosine (Table IV) but was inactivated by AOPP (Table IV; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrated that in situ accumulation of radioactivity was dependent on tissue activity of AADC. Previous studies reported that incubation of [ 3 H 2 ]-MFMT with purified AADC resulted in the formation of a stable complex [ 3 H]-MFM-dopa/AADC (Maycock et al, 1980). Pretreatment of rats with MFM-dopa resulted in almost complete inhibition of in vitro activity of AADC (Jung et al, 1984).…”
Section: Discussionmentioning
confidence: 95%
“…This methodology is based on the potential in vivo TH-catalyzed transformation of (3Ј,5Ј)- (Maycock et al, 1980). Our previous study suggested that incorporation of [ 3 H 2 ]-MFMT in brain protein metabolism was insignificant and that the in vivo metabolite of [ 3 H 2 ]-MFMT via TH activity was, as expected from previous pharmacological results, a potent and irreversible substrate for AADC (Lafargue et al, 1994).…”
Section: Introductionmentioning
confidence: 90%
“…which kills itself after the release of a stoichiometric amount of C 0 2 and F-, consistent with a decarboxylative elimination sequence and then an efficient eneamino-PLP capture by a suicidal enzymic nucleophile (95). The pharmacological consequences of such specific inactivation of these key decarboxylases are being hotly pursued (e.g., 1 1,96,97).…”
Section: Christopher Walshmentioning
confidence: 88%